Delayed oculomotor nerve palsy associated with a ruptured anterior communicating aneurysm: Case report. (August 2021) - Bizilis, Joshua C.; Simonin, Alexandre; Lind, Christopher R.
Highlights: Cranial nerve three oculomotor nerve palsy with subarachnoid haemorrhage. Microvascularisation of cranial nerve leading to nerve palsy. Anterior communicating artery aneurysm and associated cranial nerve palsy. Abstract: Background and importance: Oculomotor nerve palsy (ONP) is usually associated with posterior communicating (PCOM) aneurysms. ONP in patients with anterior circulation aneurysms are extremely rare, with only a handful of such published cases to date. There is currently no accepted mechanism to explain this clinical finding. Clinical presentation: We describe a case of a 60-year-old female that benefitted from endovascular coiling of a ruptured anterior communicating (ACOM) aneurysm. In the following days, she clinically deteriorated and benefitted from another digital subtraction angiography (DSA) with intravascular verapamil for suspected vasospasm, and subsequently developed a right ONP. Conclusion: Although classically related to PCOM aneurysm, ONP may be associated with ACOM aneurysms. The causative mechanism is unclear, but vasospasm may alter the microvascularisation of the oculomotor nerve, leading to ischemia.